Potential nitrogen mobilisation from the Yedoma permafrost domain - Jens Strauss; Maija E Marushchak; Lona van Delden; Tina Sanders; Christina Biasi; Carolina Voigt; Loeka L Jongejans; Claire Treat (Environmental Research Letters)
Permafrost regions, characterised by extensive belowground excess ice, are highly vulnerable to rapid thaw, particularly in areas such as the Yedoma domain. This region is known to freeze-lock a globally significant stock of soil nitrogen (N). However, the fate of this N upon permafrost thaw remains largely unknown. In this study, we assess the impact of climate warming on the size and dynamics of the soil N pool in (sub-)Arctic ecosystems, drawing upon recently published data and literature. Our findings suggest that climate warming and increased thaw depths will result in an expansion of the reactive soil N pool due to the larger volume of (seasonally) thawed soil. Dissolved organic N emerges as the predominant N form for rapid cycling within (sub-)Arctic ecosystems. The fate of newly thawed N from permafrost is primarily influenced by plant uptake, microbial immobilisation, changes in decomposition rates due to improved N availability, as well as lateral flow. The Yedoma domain contains substantial N pools, and the partial but increasing thaw of this previously frozen N has the potential to amplify climate feedbacks through additional nitrous oxide (N _2 O) emissions. Our ballpark estimate indicates that the Yedoma domain may contribute approximately 6% of the global annual rate of N _2 O emissions from soils under natural vegetation. However, the released soil N could also mitigate climate feedbacks by promoting enhanced vegetation carbon uptake. The likelihood and rate of N _2 O production are highest in permafrost thaw sites with intermediate moisture content and disturbed vegetation, but accurately predicting future landscape and hydrology changes in the Yedoma domain remains challenging. Nevertheless, it is evident that the permafrost-climate feedback will be significantly influenced by the quantity and mobilisation state of this unconsidered N pool.